Water Resources Management of Sedimentation Problems in Terengganu River Basin, Terengganu, Malaysia - Asma Ezzatee Mohd Razak, Nural; Khairul Amri Kamarudin, Mohd; Abd Wahab, Noorjima; Shakir Mohd Saudi, Ahmad; Hafiz Md Saad, Muhammad; Marcus Ata, Frankie; Hafizza Mohd Amran1, Nurul (International Journal of Engineering and Technology, 2018)
Water resource management is important for human well-being, ecosystems development and protection of existing water bodies from pollution and exploitation. Water resource management and sedimentation are carried out in Terengganu River Basin, Terengganu. The main objective is to study water resources management on sediment problems in the Terengganu River Basin. The Gravimetric method was used to analysis the TSS measured in mg/L. 250 ml water sample was needed for each study area (each station). Based on the cross section trend and the average downstream and middle section of the Sungai Terengganu system, the average TSS level is higher than the upper section. The minimum width allocation of river reserves to control development near the river is based on the Department of Irrigation and Drainage (DID). Finally, there are a few recommendations of sedimentation management around Terengganu River Basin that will improve the river water quality, especially in Malaysia.Â